Advances in AAC intervention: some contributions related to applied behavior analysis. (3rd July 2021) - Reichle, Joe; O'Neill, Robert E.; Johnston, Susan S.
Abstract: This article extends Dr. Bob Remington's call for collaborations between those supporting behavioral approaches and those supporting more natural developmental approaches to beginning communication intervention. This article expands areas previously discussed by Dr. Remington. Topics that are addressed include pivotal behaviors that may facilitate communication acquisition, matching law and response efficiency, generalization, maintenance, and the related topics of general case instruction (which involves an understanding of stimulus and response classes). These topics reflect contemporary areas of research that could be better integrated into translational research and have not been extensively integrated into augmentative and alternative communication (AAC) practice. Dr. Remington's article discussed the value of behavioral approaches and corresponding methodology to AAC researchers and practitioners. We agree and discuss the need for greater interaction among proponents of varying approaches to intervention.